HUBUNGAN IDENTITAS DIRI DENGAN KENAKALAN REMAJA DI SMK MUHAMMADIYAH 1 PEKANBARU - Rizki, Zakiyah "; ", Jumaini "; Hasanah, Oswati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractIdentity is something that owned by every individual with realization of their self that already have goal and option for their future in their life. The failure of established identity progress is one of factors caused teenagers turn into juvenile delinquency. The purpose of this research is to find out relationship between identity and juvenile delinquency at SMK Muhammadiyah 1 Pekanbaru. This research was designed as descriptive correlation with cross sectional approach. The samples of this research are 245 respondents taken using stratified random sampling technique. The measuring instrument using identity questionnaire consist of 10 statements and juvenile delinquency of 15 statements has done validity test and reliability. The analysis used is univariate analysis using frequency distribution and analysis using Chi square test bivariat. The result shows that adolescent which have positive identity 52 respondent (40,3%) tend to have delinquency that turn into violence. Result of Chi-square statistic test shows that P value  =0.248 >